Exploring the Mediating Role of The Balance Use of the Performance Measurement System on the Relationship Between Intellectual Capital and Firm Performance - Nhon, Hoang Thanh (Business Management and Strategy, 2021)
The purpose of this paper is to empirically explore how the balance use of performance measurement systems mediate the effects of intellectual capital dimensions including human, organizational and social capital on firm performance. The data were collected from a survey of 448 Vietnamese managers of Information and Communication Technology Sector and proposed hypotheses were tested by using partial least squares regression and a structural modeling technique which is appropriate for highly complex predictive models. Findings from hypotheses tests indicated that firms with higher level of intellectual capital dimensions place a premium on the balance use of performance measurement systems in a diagnostic and interactive style. Furthermore, the result also provides some evidences that Intellectual capital dimensions effect indirectly on firm performance through performance measurement systems.